Preparation method of biomass carbon aerogel composite material, biomass carbon aerogel composite material and application thereof

CN118580091BActive Publication Date: 2026-10-09SHENZHEN SUNWAY COMM
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410819460.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2026-10-09
Estimated Expiration
2044-06-24

AI Technical Summary

Technical Problem

然而,现有碳材料吸波性能不佳

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118580091B_ABST
    Figure CN118580091B_ABST
Patent Text Reader

Abstract

The embodiment of the application relates to the technical field of functional materials, in particular to a preparation method of a biomass carbon aerogel composite material, the biomass carbon aerogel composite material and application thereof. In the method, biomass aerogel loaded with ZIF-8 particles is immersed in a second mixed solution, a ZIF-67 layer can be grown on the outer surface of the ZIF-8 particles, and a target aerogel is obtained. The target aerogel comprises biomass aerogel and a double-layer metal organic framework formed by the ZIF-67 layer coating the outer surface of the ZIF-8 particles in the pores of the biomass aerogel. By carbonizing the target aerogel, a biomass carbon aerogel composite material loaded with Co and ZnO can be obtained. The Co has magnetism and is used for magnetic loss of electromagnetic waves, and the ZnO is used for dielectric loss of electromagnetic waves. The porous structure of the aerogel and the porous structure formed after the carbonization of the double-layer metal-organic framework can effectively improve the impedance mismatch phenomenon and improve the wave absorption performance of the biomass carbon aerogel composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of functional materials technology, and in particular to a method for preparing a biomass carbon aerogel composite material, the biomass carbon aerogel composite material, and its applications. Background Technology

[0002] With the rapid development of modern high technology, electromagnetic interference and electromagnetic compatibility problems caused by electromagnetic waves are becoming increasingly serious. These problems not only interfere with and damage electronic instruments and equipment, but also pollute the environment and harm human health. To reduce the harmful effects of electromagnetic radiation, microwave absorbing materials have gradually become a research hotspot.

[0003] Currently, materials used for microwave absorption include carbon materials, conductive polymers, and ferrites. Among them, carbon materials are considered potential microwave absorbing materials due to their high conductivity and rich, tunable pore structure. However, existing carbon materials have poor microwave absorption performance. Summary of the Invention

[0004] This application provides a method for preparing a biomass carbon aerogel composite material, the biomass carbon aerogel composite material and its application, which can improve the microwave absorption performance of carbon materials.

[0005] In a first aspect of this application, a method for preparing a biomass carbon aerogel composite material is provided, the method comprising: step a, immersing a biomass aerogel in a first mixed solution to grow ZIF-8 particles in the pores of the biomass aerogel to obtain a biomass aerogel loaded with ZIF-8 particles; step b, immersing the biomass aerogel loaded with ZIF-8 particles in a second mixed solution to grow a ZIF-67 layer on the outer surface of the ZIF-8 particles to obtain a target aerogel; and step c, carbonizing the target aerogel to obtain a biomass carbon aerogel composite material; wherein the first mixed solution comprises zinc nitrate hexahydrate, dimethylimidazole and a first methanol, and the second mixed solution comprises cobalt nitrate hexahydrate, dimethylimidazole and a second methanol.

[0006] In embodiments of this application, a biomass aerogel is immersed in a first mixed solution to grow ZIF-8 particles within the pores of the biomass aerogel, thereby obtaining a biomass aerogel loaded with ZIF-8 particles. The biomass aerogel loaded with ZIF-8 particles is then immersed in a second mixed solution to grow a ZIF-67 layer on the outer surface of the ZIF-8 particles, resulting in the target aerogel. Therefore, the target aerogel comprises a biomass aerogel and a bilayer metal-organic framework distributed within the pores of the biomass aerogel, formed by a ZIF-67 layer coating the outer surface of the ZIF-8 particles. Carbonization of the target aerogel yields a biomass carbon aerogel composite material loaded with Co and ZnO. Co is magnetic and used for magnetic loss of electromagnetic waves, while ZnO is used for dielectric loss of electromagnetic waves. In biomass carbon aerogel composites, the porous structure of the aerogel and the porous structure formed after the carbonization of the double-layer metal-organic framework can effectively improve the impedance mismatch phenomenon, reduce the reflection of electromagnetic waves by the biomass carbon aerogel composites, and improve the wave absorption performance of the biomass carbon aerogel composites.

[0007] In some embodiments, in the first mixed solution, the content of zinc nitrate hexahydrate in every 100 mL of the first methanol solution is 0.10 g to 0.25 g, and the content of dimethylimidazole in every 100 mL of the first methanol solution is 5.0 g to 6.5 g.

[0008] In some embodiments, in the second mixed solution, the content of cobalt nitrate hexahydrate in every 100 mL of the second methanol solution is 3.0 g to 4.5 g, and the content of dimethylimidazole in every 100 mL of the second methanol solution is 6.0 g to 8.5 g.

[0009] In some embodiments, prior to step b, the method further includes drying the biomass aerogel loaded with ZIF-8 particles.

[0010] In some embodiments, prior to step c, the method further includes: pre-oxidizing the target aerogel in an air atmosphere; wherein the temperature of the pre-oxidation treatment is 200°C to 220°C, and the time of the pre-oxidation treatment is 1.5h to 2.5h.

[0011] In some embodiments, the carbonization temperature is 850°C to 950°C, and the carbonization time is 1.5h to 2.5h.

[0012] In some embodiments, the biomass aerogel is a collagen fiber / polyvinyl alcohol aerogel; the preparation method of the collagen fiber / polyvinyl alcohol aerogel is as follows: collagen fibers with a particle size not exceeding 30 mesh are dispersed in water to obtain a dispersion of collagen fibers in water; the pH value of the dispersion is adjusted to 12-14, and the dispersion is stirred for 10-14 hours to obtain a collagen fiber solution; the collagen fiber solution is mixed with a polyvinyl alcohol solution to allow the collagen fibers and polyvinyl alcohol to undergo a crosslinking reaction to obtain a collagen fiber / polyvinyl alcohol gel; the collagen fiber / polyvinyl alcohol gel is freeze-dried to obtain a collagen fiber / polyvinyl alcohol aerogel.

[0013] In some embodiments, after mixing the collagen fiber solution with the polyvinyl alcohol solution, the mass ratio of the collagen fiber to the polyvinyl alcohol in the resulting mixture is in the range of 0.5 to 2.

[0014] It should be understood that the description in the Summary of the Invention section is not intended to limit the key or essential features of this disclosure, nor is it intended to restrict the scope of this disclosure. Other features of this disclosure will become readily apparent from the following description. Attached Figure Description

[0015] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments of the present invention will be briefly described below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.

[0016] Figure 1 This is a schematic flowchart illustrating the preparation method of biomass carbon aerogel composite material provided in some embodiments of this application. Detailed Implementation

[0017] The principles and spirit of this disclosure will be described below with reference to several exemplary embodiments illustrated in the accompanying drawings. It should be understood that these specific embodiments are described merely to enable those skilled in the art to better understand and implement this disclosure, and are not intended to limit the scope of this disclosure in any way. In the following description and claims, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art.

[0018] As used herein, the term "comprising" and similar terms should be understood as open-ended inclusion, i.e., "including but not limited to". The term "based on" should be understood as "at least partially based on". The term "an embodiment" or "the embodiment" should be understood as "at least one embodiment". The terms "first", "second", etc., may refer to different or the same objects and are used only to distinguish the objects referred to, without implying a particular spatial order, temporal order, order of importance, etc., of the objects referred to.

[0019] To facilitate understanding, ZIF-8, ZIF-67, and related concepts will be introduced below.

[0020] Metal-organic frameworks (MOFs) are coordination compounds with periodic structures, assembled through coordination bonds using organic ligands as linkers and metal ions (or metal ion clusters) as nodes. MOFs are highly ordered porous materials. In the synthesis of MOFs, besides the influence of ligands and metal ions, other factors also play a role, such as reaction temperature, solvent, pH, pressure, and the ratio and concentration of ligands and metal salts. These factors can affect the self-assembly process of MOFs, thus influencing their structure and, consequently, their properties. As a novel material, metal-organic frameworks have become a research hotspot in various fields.

[0021] Zeolitic imidazolate frameworks (ZIFs) belong to the class of metal-organic frameworks (MOFs). In ZIFs, organic imidazolates are cross-linked to transition metals, forming a tetrahedral framework. ZIFs are a novel type of porous material that combines the high stability of inorganic zeolites with the high porosity and organic functionality of MOFs. ZIF-8 is a porous crystalline material formed by the self-assembly of zinc ions and 2-methylimidazolium. The zeolite-type imidazolate metal-organic framework ZIF-67 is based on the divalent transition metal Co. 2+ Porous crystalline materials with zeolite topology constructed with imidazole ligands. The metal nodes of ZIF-67 are Co ions, while the metal nodes of ZIF-8 are Zn ions.

[0022] For example, Figure 1 The present application provides a flowchart of a method for preparing a biomass carbon aerogel composite material according to some embodiments, the method comprising:

[0023] Step a: Immerse the biomass aerogel in the first mixed solution to grow ZIF-8 particles in the pores of the biomass aerogel to obtain a biomass aerogel loaded with ZIF-8 particles.

[0024] In this embodiment, aerogel is a low-density, high-porosity material. When a gel loses most of its solvent, resulting in a much lower liquid content than solid content, or when the gel's spatial network structure is filled with gas, it appears as a solid; this is called an aerogel, also known as a dry gel. The first mixed solution includes zinc nitrate hexahydrate, dimethylimidazole, and methanol. By immersing the biomass aerogel in the first mixed solution, ZIF-8 particles can be grown in the pores of the biomass aerogel, resulting in a biomass aerogel loaded with ZIF-8 particles.

[0025] Specifically, in some embodiments, to improve the microwave absorption performance of the biomass carbon aerogel composite material, the content of zinc nitrate hexahydrate in each 100 mL of the first methanol solution is 0.10 g-0.25 g, and the content of dimethylimidazole in each 100 mL of the first methanol solution is 5.0 g-6.5 g. In some embodiments of this application, to further improve the microwave absorption performance of the biomass carbon aerogel composite material, the content of zinc nitrate hexahydrate and dimethylimidazole in each 100 mL of the first methanol solution is 0.2 g and 6.15 g, respectively, or the content of zinc nitrate hexahydrate and dimethylimidazole in each 100 mL of the first methanol solution is 0.15 g and 5.45 g, respectively.

[0026] In some embodiments, step a specifically includes: immersing the biomass aerogel in a first mixed solution at room temperature for 3-5 hours, followed by drying the biomass aerogel to obtain a biomass aerogel loaded with ZIF-8 particles. The drying process can specifically be vacuum drying at a temperature of 75°C-85°C.

[0027] In some embodiments, the biomass aerogel is specifically a biomass collagen fiber / polyvinyl alcohol aerogel. The preparation method of the biomass collagen fiber / polyvinyl alcohol aerogel is as follows: collagen fibers with a particle size not exceeding 30 mesh are dispersed in water to obtain a dispersion of collagen fibers in water; the pH value of the dispersion is adjusted to 12-14, and the dispersion is stirred for 10-14 hours to obtain a collagen fiber solution; the collagen fiber solution is mixed with a polyvinyl alcohol solution to allow the collagen fibers and polyvinyl alcohol to undergo a cross-linking reaction, thereby obtaining a collagen fiber / polyvinyl alcohol gel; the collagen fiber / polyvinyl alcohol gel is freeze-dried to obtain a collagen fiber / polyvinyl alcohol aerogel. The collagen fibers are a fiber composition mainly containing collagen, amino acids, glycine, proline, and hydroxyproline.

[0028] In some embodiments, the preparation method of biomass collagen fiber / polyvinyl alcohol aerogel is as follows: Collagen fibers with a particle size not exceeding 30 mesh are dispersed in ultrapure water to obtain a dispersion of collagen fibers in water; the pH of the dispersion is adjusted to 12-14 with NaOH; the dispersion is vigorously stirred at room temperature, and the reactants in the dispersion react for 10-14 hours during the stirring process to obtain a collagen fiber solution; an appropriate amount of polyvinyl alcohol is dissolved in ultrapure water, and the mixture is vigorously stirred at 80-90°C to obtain a polyvinyl alcohol solution; an appropriate amount of collagen fiber solution and an appropriate amount of polyvinyl alcohol solution are taken and stirred thoroughly, and allowed to stand for more than 24 hours to allow the collagen fibers and polyvinyl alcohol to undergo a cross-linking reaction automatically and gel to obtain a collagen fiber / polyvinyl alcohol gel; the collagen fiber / polyvinyl alcohol gel is poured into a mold, and the mold containing the collagen fiber / polyvinyl alcohol gel is placed at -40°C for freeze-drying for 48 hours to obtain a collagen fiber / polyvinyl alcohol aerogel.

[0029] In some embodiments, collagen fibers need to be prepared before dispersing them in water. The specific preparation method of collagen fibers is as follows: after crushing the collagen fiber raw material with a pulverizer, collagen fibers with a mesh size of less than 30 mesh are screened out with a sieve, washed with ultrapure water for 10 to 14 hours, and then dried at 40°C to 50°C.

[0030] Step b: Immerse the biomass aerogel loaded with ZIF-8 particles in a second mixed solution to grow a ZIF-67 layer on the outer surface of the ZIF-8 particles to obtain the target aerogel.

[0031] In some embodiments, a biomass aerogel loaded with ZIF-8 particles is immersed in a second mixed solution to grow a ZIF-67 layer on the outer surface of the ZIF-8 particles, thereby obtaining the target aerogel; wherein, the second mixed solution is a mixed solution of cobalt nitrate hexahydrate, dimethylimidazole, and second methanol, and in the target aerogel, a double-layer metal-organic framework material formed by the ZIF-67 material layer covering the outer surface of the ZIF-8 particles is distributed in the pores of the biomass aerogel.

[0032] In some embodiments, step b is specifically as follows: At room temperature, the biomass aerogel loaded with ZIF-8 particles is immersed in a second mixed solution for 2-4 hours, followed by drying to obtain the target aerogel. The drying method is vacuum drying, and the drying time can be 10-14 hours. The drying temperature is 75°C-85°C.

[0033] Specifically, in some embodiments, to improve the microwave absorption performance of the biomass carbon aerogel composite material, the content of cobalt nitrate hexahydrate in each 100 mL of the second methanol solution is 3.0 g-4.5 g, and the content of dimethylimidazole in each 100 mL of the second methanol solution is 6.0 g-8.5 g. In some embodiments of this application, to further improve the microwave absorption performance of the biomass carbon aerogel composite material, the content of cobalt nitrate hexahydrate and dimethylimidazole in each 100 mL of the second methanol solution is 3.34 g and 6.15 g, respectively, or the content of cobalt nitrate hexahydrate and dimethylimidazole in each 100 mL of the second methanol solution is 4.34 g and 8.15 g, respectively.

[0034] Step c: Carbonize the target aerogel to obtain a biomass carbon aerogel composite material.

[0035] In this embodiment, the target aerogel is carbonized to obtain a biomass carbon aerogel composite material loaded with magnetic particles. Specifically, in some embodiments, the carbonization temperature is 800℃~900℃, and the heating rate during the heating process is 1.5℃ / min~2.5℃ / min.

[0036] In some embodiments, before carbonizing the target aerogel, it is necessary to pre-oxidize the target aerogel in an air atmosphere; wherein the pre-oxidation treatment temperature is 200℃~220℃, and the pre-oxidation treatment time is 1.5h~2.5h. In this embodiment, pre-oxidizing the target aerogel can prevent the collapse of the porous structure of the target aerogel. In some embodiments of this application, in order to improve the effect of the pre-oxidation treatment, the heating rate during the pre-oxidation treatment is 9℃ / min~11℃ / min.

[0037] In embodiments of this application, a biomass aerogel is immersed in a first mixed solution to grow ZIF-8 particles within the pores of the biomass aerogel, thereby obtaining a biomass aerogel loaded with ZIF-8 particles. The biomass aerogel loaded with ZIF-8 particles is then immersed in a second mixed solution to grow a ZIF-67 layer on the outer surface of the ZIF-8 particles, resulting in the target aerogel. Therefore, the target aerogel comprises a biomass aerogel and a bilayer metal-organic framework distributed within the pores of the biomass aerogel, formed by a ZIF-67 layer coating the outer surface of the ZIF-8 particles. Carbonization of the target aerogel yields a biomass carbon aerogel composite material loaded with Co and ZnO. Co is magnetic and used for magnetic loss of electromagnetic waves, while ZnO is used for dielectric loss of electromagnetic waves. In biomass carbon aerogel composites, the porous structure of the aerogel and the porous structure formed after the carbonization of the bilayer metal-organic framework can effectively improve impedance mismatch, reduce the reflection of electromagnetic waves by the biomass carbon aerogel composite, and improve the microwave absorption performance of the biomass carbon aerogel composite. Biomass carbon has the characteristics of complex pore structure, good conductivity, high specific surface area and renewability, making it an excellent microwave absorbing material.

[0038] Several embodiments of this application are provided below.

[0039] Example 1

[0040] Place 100 mL of ultrapure water in the first container, disperse 5 g of dried collagen fibers in the ultrapure water in the first container, and adjust the pH of the solution in the first container to 13 with 5 mol / L NaOH; at room temperature, stir the solution in the first container vigorously to allow the collagen fibers and NaOH in the first container to react for 12 h to obtain a collagen fiber solution.

[0041] Place 9 mL of ultrapure water into the second container. Dissolve 1 g of polyvinyl alcohol in the ultrapure water in the second container, and stir the mixture in the second container vigorously at 85 °C to obtain a polyvinyl alcohol solution.

[0042] 8 mL of collagen fiber solution and 2 mL of polyvinyl alcohol solution were mixed and stirred thoroughly. The mixture was allowed to stand for 24 hours to allow the collagen fibers and polyvinyl alcohol to undergo an automatic cross-linking reaction and gel. The gel was then poured into a plastic mold to obtain a collagen fiber / polyvinyl alcohol gel. The collagen fiber / polyvinyl alcohol gel was then freeze-dried at -40°C for 48 hours to obtain a collagen fiber / polyvinyl alcohol aerogel.

[0043] Collagen fiber / polyvinyl alcohol aerogel was immersed in 100 mL of a first methanol solution containing 0.2 g zinc nitrate hexahydrate and 6.15 g dimethylimidazole at room temperature for 4 hours, and then vacuum dried at 80 °C overnight to obtain collagen fiber / polyvinyl alcohol aerogel loaded with ZIF-8.

[0044] At room temperature, collagen fiber / polyvinyl alcohol aerogel loaded with ZIF-8 was immersed in 100 mL of a second methanol solution containing 3.34 g cobalt nitrate hexahydrate and 6.15 g dimethylimidazole for 3 hours, and then vacuum dried overnight at 80 °C to obtain the target aerogel.

[0045] The target aerogel was placed in an oven at 220℃ for 2 hours for pre-oxidation, with a heating rate of 10℃ / min. The pre-oxidized target aerogel was then carbonized at 850℃ for 2 hours with a heating rate of 2℃ / min to obtain the biomass carbon aerogel composite material.

[0046] Example 2

[0047] Place 100 mL of ultrapure water in the third container, and disperse 5 g of dried collagen fibers in the ultrapure water in the third container; adjust the pH of the solution in the third container to 13 with 5 mol / L NaOH, and stir the solution in the first container vigorously at room temperature to allow the collagen fibers in the third container to react with NaOH for 12 h to obtain a collagen fiber solution.

[0048] Place 9 mL of ultrapure water into the fourth container. Dissolve 1 g of polyvinyl alcohol in the ultrapure water in the fourth container, and stir the mixture in the fourth container vigorously at 85 °C to obtain a polyvinyl alcohol solution.

[0049] Mix 6 mL of collagen fiber solution and 4 mL of polyvinyl alcohol solution, stir thoroughly, and let stand for 24 h. The collagen fibers and polyvinyl alcohol will automatically undergo a cross-linking reaction and gel. Then pour the mixture into a plastic mold to obtain a collagen fiber / polyvinyl alcohol gel. Freeze-dry the collagen fiber / polyvinyl alcohol gel at -50℃ for 48 h to obtain a collagen fiber / polyvinyl alcohol aerogel.

[0050] Collagen fiber / polyvinyl alcohol aerogel was immersed in 100 mL of a first methanol solution containing 0.15 g zinc nitrate hexahydrate and 5.45 g dimethylimidazole at room temperature for 3 hours, and then vacuum dried at 80 °C overnight to obtain collagen fiber / polyvinyl alcohol aerogel loaded with ZIF-8.

[0051] Collagen fiber / polyvinyl alcohol aerogel loaded with ZIF-8 was immersed in 100 mL of a second methanol solution containing 4.34 g of cobalt nitrate hexahydrate and 8.15 g of dimethylimidazole at room temperature for 4 hours, and then vacuum dried at 80 °C overnight to obtain the target aerogel.

[0052] The target aerogel was placed in an oven at 210℃ for 2 hours for pre-oxidation, with a heating rate of 10℃ / min. The pre-oxidized target aerogel was then carbonized at 900℃ for 2 hours with a heating rate of 2℃ / min to obtain the biomass carbon aerogel composite material.

[0053] The microwave absorption performance of the biomass carbon aerogel composite materials provided in Examples 1 and 2 were tested respectively. The test results show that when the thickness of the biomass carbon aerogel composite material provided in Example 1 is 2.32 mm, the material has the lowest reflection loss value (RL) at 6.56 GHz. min The effective absorption band is -63.4 dB, with an effective absorption frequency band up to 5.25 GHz; when the thickness of the biomass carbon aerogel composite material provided in Example 2 is 2.84 mm, the RL of this material at 8.48 GHz is... min It has a strength of -70.8dB and an effective absorption band of up to 5.56GHz.

[0054] Therefore, the biomass carbon aerogel composite material provided in this application has good microwave absorption properties. This application embodiment obtains the target aerogel by in-situ growth of a bilayer metal-organic framework within the pores of the biomass aerogel; the porous structure obtained after carbonization of the target aerogel can effectively reduce the impedance mismatch of the biomass carbon aerogel composite material and reduce the reflection of electromagnetic waves by the biomass carbon aerogel composite material.

[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; under the concept of the present invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of different aspects of the present invention as described above, which are not provided in detail for the sake of brevity; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a biomass carbon aerogel composite material, characterized in that, The method includes: Step a: Immerse the biomass aerogel in the first mixed solution to grow ZIF-8 particles in the pores of the biomass aerogel to obtain a biomass aerogel loaded with ZIF-8 particles. Step b: Immerse the biomass aerogel loaded with ZIF-8 particles in the second mixed solution to grow a ZIF-67 layer on the outer surface of the ZIF-8 particles to obtain the target aerogel. Step c: Carbonize the target aerogel to obtain a biomass carbon aerogel composite material; wherein, before step c, the method further includes: pre-oxidizing the target aerogel in an air atmosphere; wherein the temperature of the pre-oxidation treatment is 200℃~220℃, and the time of the pre-oxidation treatment is 1.5h~2.5h. The first mixed solution comprises zinc nitrate hexahydrate, dimethylimidazole and a first methanol solution, and the second mixed solution comprises cobalt nitrate hexahydrate, dimethylimidazole and a second methanol solution. In the first mixed solution, the content of zinc nitrate hexahydrate in every 100 mL of the first methanol solution is 0.10 g to 0.25 g, and the content of dimethylimidazole in every 100 mL of the first methanol solution is 5.0 g to 6.5 g. In the second mixed solution, the content of cobalt nitrate hexahydrate in every 100 mL of the second methanol solution is 3.0 g to 4.5 g, and the content of dimethylimidazole in every 100 mL of the second methanol solution is 6.0 g to 8.5 g.

2. The method according to claim 1, characterized in that, Prior to step b, the method further includes: The biomass aerogel loaded with ZIF-8 particles was dried.

3. The method according to claim 1, characterized in that, The carbonization treatment temperature is 850℃~950℃, and the carbonization treatment time is 1.5h~2.5h.

4. The method according to any one of claims 1-3, characterized in that, The biomass aerogel is a collagen fiber / polyvinyl alcohol aerogel; The preparation method of the collagen fiber / polyvinyl alcohol aerogel is as follows: Collagen fibers with a particle size of no more than 30 mesh are dispersed in water to obtain a dispersion of collagen fibers in water. The pH of the dispersion was adjusted to 12-14, and the dispersion was stirred for 10-14 hours to obtain a collagen fiber solution. The collagen fiber solution is mixed with a polyvinyl alcohol solution to allow the collagen fiber and the polyvinyl alcohol to undergo a cross-linking reaction, thereby obtaining a collagen fiber / polyvinyl alcohol gel. The collagen fiber / polyvinyl alcohol gel was freeze-dried to obtain collagen fiber / polyvinyl alcohol aerogel.

5. The method according to claim 4, characterized in that, After mixing the collagen fiber solution with the polyvinyl alcohol solution, the mass ratio of the collagen fiber to the polyvinyl alcohol in the resulting mixture is in the range of 0.5 to 2.

6. A biomass carbon aerogel composite material, characterized in that, The biomass carbon aerogel composite material is prepared by the method according to any one of claims 1-5.

7. The application of a biomass carbon aerogel composite material prepared by the method according to any one of claims 1-5 in the field of electromagnetic wave absorption.

Citation Information

Patent Citations

  • Polyvinyl alcohol-based carbon aerogel using waste leather as carbon source, and preparation method thereof

    CN111977631A

  • Cobalt-loaded Nb2CTx / carbon aerogel as well as preparation method and application thereof

    CN116099463A